Coordination in functional traits of Populus euphratica leaves under salt stress - Li, Duan; Si, Jianhua; Ren, Xiaozong; Li, Jiyan (Frontiers in Forests and Global Change, 2023)
Leaf functional traits allow plant survival and maintain their ecosystem function. Salinity affects leaf functional traits, but coordination among leaf functional traits is poorly known and may depend on salt severity. To increase our understanding of the coordination of leaf functional traits under salt stress, we determined hydraulic, gas exchange, and physiological and biochemical parameters in Populus euphratica Oliv. (P. euphratica) grown in salinity treatments, as well as gas exchange parameters under different CO2 concentrations. We found that P. euphratica can reinforce its hydraulic capacity by an increase in the water transfer efficiency of both leaves and stems when a salinity threat occurs at a specific duration of stress, and stems were more adaptable than leaves. Leaf economic traits in P. euphratica were consistent with leaf hydraulic traits at medium levels of salt stress, with inconsistency during the onset and late stages of salt stress. There was no biochemical limitation under severe not fatal salinity conditions and CO2 enrichment of P. euphratica had a greater effect on leaf economic traits. The exclusion of toxic ions based on water availability and osmotic mechanisms in leaves contributed to salt tolerance when P. euphratica was exposed to salinity stress. There also was a physiologically adaptive mechanism for plants during increasing salt stress. Leaf osmotic traits in P. euphratica can coordinate with leaf economic and with leaf hydraulic traits, and form a defense mechanism to reduce salt damage and guarantee growth under saline conditions. In conclusion, P. euphratica, the main constructional species of riparian forests, adapts to saline environments by adjustment and coordination among leaf functional traits, ensuring survival. These results provide a scientific basis for riparian forest restoration.